Guidance note for peace-informed programming at the Green Climate Fund: Transport - Scartozzi, Cesare M; Caroli, Giulia; Sarzana, Carolina; Läderach, Peter R.D.; Pacillo, Grazia; Hyslop, Daniel; Hahn, Andreas Luis; Azar, Elio; Nicatore, Giorgia; Brown, Oliver; Hassamal, Komal; Ehmsen, Simon (2023)
Transport-related projects in Fragile and Conflict-affected Settings (FCS) encounter operational risks and challenges and have the potential to ignore and/or exacerbate peace and conflict dynamics by affecting the interplay of social, political, economic, cultural, and environmental factors that drive fragility, conflict, and violence. Being insufficiently aware of the conflict dynamics may inadvertently contribute to conflict and undermine the achievement of the project’s goals, as well as undermining its potential to contribute to peace and stability. For example, people living in rural areas are highly dependent on transportation to access markets in larger cities, and any changes in transport methods, whether related to conflict or projects interventions, carry a risk of disruption. Yet opportunities exist for projects to enhance trade links through improved transport thus contributing to better economic opportunities for rural producers